Comparison of the efficacy of Philos plate and Multiloc intramedullary nail in the treatment of complex proximal humeral fractures with osteoporosis in the elderly - Liu, Qian; Cao, Zongbing; Liu, Jing; Liu, Zhiyong; Zhang, Wenbo (Frontiers in Surgery, 2025)
IntroductionProximal humeral fractures are common in elderly patients with osteoporosis. Complex three- or four-part fractures often require surgical intervention. Philos locking plates and Multiloc intramedullary nails are widely used, but their comparative effectiveness in osteoporotic elderly patients remains uncertain.MethodsA retrospective study was performed on 90 elderly patients (aged 70–95 years) with Neer three- or four-part proximal humeral fractures treated between January 2021 and December 2023. Patients received either Philos plate fixation (n = 50) or Multiloc intramedullary nail fixation (n = 40). Clinical data included incision length, operative time, blood loss, complications, and functional outcomes. Pain was assessed via VAS, and shoulder function via Constant-Murley scores at 1 week, 1 month, and 12 months postoperatively.ResultsBoth groups achieved fracture healing and functional improvement. Compared to the Philos group, the Multiloc group had shorter incisions, less blood loss, and shorter operative time (all P < 0.05). VAS scores were lower and Constant-Murley scores higher in the Multiloc group at all time points (P < 0.05). Complication rates were lower in the Multiloc group (10% vs. 20%).DiscussionBoth techniques are effective, but Multiloc intramedullary nail fixation offers superior early outcomes and fewer complications. It may be preferable for elderly patients with osteoporotic proximal humeral fractures when proper surgical technique is ensured.